2007
DOI: 10.1093/carcin/bgm126
|View full text |Cite
|
Sign up to set email alerts
|

Acteoside inhibits human promyelocytic HL-60 leukemia cell proliferation via inducing cell cycle arrest at G0/G1 phase and differentiation into monocyte

Abstract: We investigated the in vitro effects of acteoside on the proliferation, cell cycle regulation and differentiation of HL-60 human promyelocytic leukemia cells. Acteoside inhibited the proliferation of HL-60 cells in a concentration- and time-dependent manner with an IC50, approximately 30 microM. DNA flow cytometric analysis indicated that acteoside blocked cell cycle progression at the G1 phase in HL-60 human promyelocytic leukemia cells. Among the G1 phase cell cycle-related proteins, the levels of cyclin-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…[21][22][23] Cyclin D1, CDK4 and E2F1 are important proteins promoting transition of G 1 to S phase. [24][25][26][27] On the other hand, p27 acts as the inhibitor of transition of G 1 to S phase. [28][29][30] In summary, SAD downregulated the expressions of proteins promoting transition of G 1 /S and upregulated the expressions of proteins inhibiting transition of G 1 /S, which was coincident with PI staining and flow cytometry analysis showing increase of G 1 content.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Cyclin D1, CDK4 and E2F1 are important proteins promoting transition of G 1 to S phase. [24][25][26][27] On the other hand, p27 acts as the inhibitor of transition of G 1 to S phase. [28][29][30] In summary, SAD downregulated the expressions of proteins promoting transition of G 1 /S and upregulated the expressions of proteins inhibiting transition of G 1 /S, which was coincident with PI staining and flow cytometry analysis showing increase of G 1 content.…”
Section: Discussionmentioning
confidence: 99%
“…1) is a well-studied PeG that consists of several chemical groups, including caffeic acid, 3,4-dihydroxyphenylethanol, glucose, and rhamnose (Hwang et al 2010). It has been reported that acteoside has extensive biological activities including antioxidant (Chiou et al 2004;He et al 2000), anti-inflammatory (Lee et al 2005(Lee et al , 2006, hepatoprotective (Xiong et al 1999;Zhao et al 2009), cell apoptosis regulation activities (Ohno et al 2002;Xiong et al 1999;Yang and Pu 2006) and cytotoxicity against various tumor cells (Kunvari et al 1999;Lee et al 2007). It may be developed into a promising medication (He et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is a report that four glycosides such as acteoside, isoacteoside, rutin and hisrutrin may be major components of A. distichum (Oh et al, 2003) and acteoside reduced cyclin D1 protein level in human leukemia cell line, HL-60 (Lee et al, 2007). However, it is not clear that the reduction of cyclin D1 protein level by acteoside results from transcriptional regulation or proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%